Influence of Vermicompost Fertilizer and Water Deficit Stress on Morpho-Physiological Features of Chickpea (Cicer arietinum L. cv. karaj). Issue 3 (3rd July 2017) - Amiri, Hamzeh; Ismaili, Ahmad; Hosseinzadeh, Saeed Reza
ABSTRACT: One goal in the face of deficit water conditions is to increase growth and yield. Agro-industrial production frequently causes environmental pollution by using chemical fertilizers. In recent decades, bio-fertilizers such as vermicompost have been used as a safe alternative to chemical fertilizer. The present study considered the response of the chickpea to different combinations of vermicompost and water deficit stress in a greenhouse environment. Plant response was determined by measuring a range of morpho-physiologic parameters. The treatments were addition of 0%, 10%, 20%, and 30% of vermicompost to soil, and water deficit stress at the following levels: non-stress (100% of field capacity), moderate water stress (75% of field capacity), and severe water stress (25% of field capacity). The results showed that vermicompost had a significant effect on all traits under stress and non-stress conditions. The vermicompost treatments under non-stress conditions significantly increased plant height, number of pods, leaf area, stem and leaf dry weight, pod dry weight, chlorophyll a, carotenoid, total chlorophyll content, CO2 assimilation rate, internal CO2 concentration, and water-use efficiency over that of the control condition. The addition of 30% vermicompost under moderate and severe water stress conditions significantly increased plant height, number of pods, leaf area, leaf dry weight, carotenoids, and water-use efficiency over that of the control level. This study confirmed that vermicompost improved the morphological features, soil biological activity, and quality of the chickpea, but did not positively influence the physiological features under moderate and severe water deficit stress.